Bioactive titanium composites for bone implant applications. Issue 1 (September 2021) - Krishna, Emani Siva; Suresh, G.; Ratna Sunil, B.; Dumpala, Ravikumar
Abstract: Development of titanium (Ti) based implants has revolutionized the application of materials engineering to address several challenges associated with other metallic implants. Ti exhibit excellent biocompatibility, nontoxicity and lowers the stress shielding effect. However, bio-inert nature of titanium is a limitation and therefore, several surface engineering strategies are adopted to promote bioactivity. Higher bioactivity helps to improve the healing rate by accelerating the implant tissue interactions. On the other hand, developing Ti based composites by incorporating bioactive ceramic phases is another promising route to develop bioactive Ti implants. In the present review, the role of addition of bioactive ceramic phases on tailoring the properties of Ti for bone implant applications is presented. Different processing routes to incorporate bioceramic particles into Ti are also discussed with a brief discussion on future scope of Ti based composites for biomedical implant applications.